The Rise of Economic Societies in the Eighteenth Century
X, 398 p.
Keywords: This collection of essays explores the emergence of economic societies in the British Isles and their development into a European, American and global reform movement in the eighteenth century. Its fourteen contributions demonstrate the intellectual horizons and international networks of this widespread and influential phenomenon.